PrimeLife guide to personal success : a planning guide for the 40-plus generation - Haynes, Marion E. (Crisp Pub. Menlo ParkUS, 1996)
Examines in detail the seven pillars of life. Lists and briefly describes ten dimensions of the lives of balanced, successful people. Assists readers to prioritize areas that need attention and to develop plans for effecting improvement.